2015
DOI: 10.3892/ol.2015.3806
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer resistance protein (BCRP)-containing circulating microvesicles contribute to chemoresistance in breast cancer

Abstract: Abstract. At present, one of the major problems of cancer therapy is drug resistance. Breast cancer resistance protein (BCRP), a marker of the multidrug-resistant phenotype, affects drug absorption, distribution, metabolism, and excretion in normal tissues. Meanwhile, extracellular vesicles (EVs) have attracted increasing attention as a medium of cell-to-cell communication. However, the association between BCRP and circulating EVs remains unclear. The present study demonstrated that patients who did not respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…In the context of the neo-adjuvant treatment of breast carcinoma, elevated levels of the EV-bound MDR-glycoprotein BCRP were detected in non-responders compared to responders or treatment naïve patients 14 . In addition, the receptor channel protein TRCP5, a known regulator of multidrug resistance glycoprotein-P, was required for EV formation in Studying EV-based therapies, some groups have explored the utilization of EVs as therapeutic delivery systems.…”
Section: Evs As 'Real-time' Biomarkers During Cancer Therapiesmentioning
confidence: 99%
“…In the context of the neo-adjuvant treatment of breast carcinoma, elevated levels of the EV-bound MDR-glycoprotein BCRP were detected in non-responders compared to responders or treatment naïve patients 14 . In addition, the receptor channel protein TRCP5, a known regulator of multidrug resistance glycoprotein-P, was required for EV formation in Studying EV-based therapies, some groups have explored the utilization of EVs as therapeutic delivery systems.…”
Section: Evs As 'Real-time' Biomarkers During Cancer Therapiesmentioning
confidence: 99%
“…BCRP was found to be upregulated at the mRNA and protein levels in circulating EVs from cancer patients that had a poor response to chemotherapy. They also found that BCRP and flotillin-2 were upregulated in tumor samples from nonresponsive patients [30]. Flotillin-2 has been shown to be involved in various cellular processes such as cell adhesion and signal transduction through receptor tyrosine kinases as well as in cellular trafficking pathways [31].…”
Section: Evs In Breast Cancer Therapy Monitoringmentioning
confidence: 98%
“…Chen et al [30] (Table 1) analyzed the relationship between breast cancer resistance protein (BCRP) and circulating EVs (microvesicles). The group showed that the levels of BCRP in patients who did not respond or had progressive/stable disease following chemotherapy were higher compared to those that did not receive chemotherapy.…”
Section: Evs In Breast Cancer Therapy Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…EVs can reprogram cancer cell metabolism, mediate therapeutic drug interactions, and are implicated in driving the transformation of fibroblasts and other TME cells to a CAF phenotype. [61][62][63] EVs can in turn enhance the metastatic potential of the tumour such as up-regulating MMP-9 expression in melanoma cells and reprogramming cancer cells with enhanced metastatic potential. 64 Le et al 65 showed that EVs containing miR-200 can alter gene programming and promote MET.…”
Section: Contribution Of the Tme To Metastasis In Breast Cancermentioning
confidence: 99%